Contemporary Yoruba Heroes in Public Sculpture - Tolulope O. Sobowale; Kehinde Adepegba; Johnson O. Oladesu (Yoruba Studies Review, 2023)
From ancient times, the Yorùbá people held in high esteem people who occupied reputable positions in their society. As such, at the departure of such people, they are immortalized in sculptural forms by the living.  Examples of this is Ako figures among the Ọ̀wọ̀ people, bronze figures representing past Ooni and Sango symbol which is represented in a carved double axe wand. This tradition continues in the contemporary time whereby some Yorùbá heroes are also rendered in sculptural images adorning selected open spaces. The paper thus, aims at examining some selected Yorùbá figures in public sculpture with a view to classifying and providing information about their life, contributions and philosophy that serve as good examples to the public. In achieving this, formal and contextual analytical methods are used.